Gender and Violence in Haiti : Women's Path from Victims to Agents - Faedi Duramy, Benedetta (Book collections on Project MUSE., 2014)
Women in Haiti are frequent victims of sexual violence and armed assault. Yet an astonishing proportion of these victims also act as perpetrators of violent crime, often as part of armed groups. In Gender and Violence in Haiti, award-winning legal scholar Benedetta Faedi Duramy visits Haiti to discover why these women act in such destructive ways and what might be done to stop this tragic cycle of violence.